ECONOMIC FEASIBILITY OF INVESMENT ALTERNATIVES FOR REDUCING TORULA YEAST' PRODUCTION COST - Torres Fernández, Alfredo; Díaz de los Ríos, Manuel; Saura Laria, Gustavo (Centro Azúcar Journal, 2016)
The prices of ammonium salts which are used in the torula yeast production technology are very high nowadays. In the other hand, this technology has very high energy costs which are consumed by blowers in fermentation, separators machines and in the concentration and drying of yeast. In this paper, different technical alternatives are analyzed for reducing the production cost of torula yeast, through changes in production inputs, electric motors and the replacement of a portion of the fuel used for drying by biogas. Then, the economic feasibility in both currencies is evaluated for practical application.